2018
DOI: 10.1371/journal.ppat.1007290
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal transcriptomic characterization of the immune response to acute hepatitis C virus infection in patients with spontaneous viral clearance

Abstract: Most individuals exposed to hepatitis C virus (HCV) become persistently infected while a minority spontaneously eliminate the virus. Although early immune events influence infection outcome, the cellular composition, molecular effectors, and timeframe of the host response active shortly after viral exposure remain incompletely understood. Employing specimens collected from people who inject drugs (PWID) with high risk of HCV exposure, we utilized RNA-Seq and blood transcriptome module (BTM) analysis to charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 49 publications
1
47
0
Order By: Relevance
“…Thus, these two strains can serve as ideal materials to investigate the factors of M. bovis pathogenesis. Furthermore, PBMCs are clinically relevant cells with well-established roles in host immune responses to microbial pathogens [16]. The objective of this study was to reveal the underlying mechanism for pathogenesis of virulent P1 strain and immunity of attenuated P150 strain by performing a comparative transcriptome analysis of PBMCs from calves infected with both strains and confirming the transcriptome findings using the data from the blood and lung tissues and gross pathology of the experimental cattle.…”
Section: Introductionmentioning
confidence: 90%
“…Thus, these two strains can serve as ideal materials to investigate the factors of M. bovis pathogenesis. Furthermore, PBMCs are clinically relevant cells with well-established roles in host immune responses to microbial pathogens [16]. The objective of this study was to reveal the underlying mechanism for pathogenesis of virulent P1 strain and immunity of attenuated P150 strain by performing a comparative transcriptome analysis of PBMCs from calves infected with both strains and confirming the transcriptome findings using the data from the blood and lung tissues and gross pathology of the experimental cattle.…”
Section: Introductionmentioning
confidence: 90%
“…Also, the dysfunction of HCV-infected PBMCs leads to immune function decline, and it becomes more difficult for the host to clear intrahepatic HCV [16]. Moreover, recent studies have shown that PBMCs may reflect the alterations of intracellular pathways occurring during HCV-related liver diseases [17], being the innate antiviral response against acute HCV not restricted to the liver [18].…”
Section: Introductionmentioning
confidence: 99%
“…We will also learn about vertical regulation of T cell processes through epigenetic, transcriptional, translational, and post-translational processes. These insights will help understand cross-talk between T cells and different immune cell types or other components of the host immune response by integrating data from many different emerging studies [90] as well as using unbiased parallel analysis of different immune cells with technologies such as 10x or Seq-Well. There has never been a more exciting time to study HCV immunology.…”
Section: Discussionmentioning
confidence: 99%